The effect of four weeks exposure to high-altitude on anaerobic performance - Grzywacz, T.; Ziemann, E.; Szymczak, R.; Szczesna-Kaczmarek, A. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: High-altitude exposure impairs both maximal aerobic and anaerobic performance. It`s known that maximal aerobic power (VO2 max) decreases proportionally to increasing altitude. It`s consequence of reduced oxygen pressure (PO2) and low hemoglobin O2 saturation. Many authors suggested that anaerobic muscle power output and blood lactate accumulation during short supramaximal exercise are substantially unaffected by hypoxia if the length of exposure does not exceed 4-5 weeks. After this period decrease of muscle mass may become an important factor contributing to the maximal anaerobic muscle power output. However there is no evidence that anaerobic metabolism processes were up regulated to sustain energy consumption during chronic hypoxia, but on the other hand, enhanced fatty acid metabolism may spare carbohydrate for metabolic fuel under conditions of extreme hypoxic limitation. Due to this fact we examined effect of four weeks exposure to high-altitude on body composition and anaerobic performance. Methods: Nine healthy male volunteered for this study. They were members of high-mountain "Pamir 2005 Expedition", and they have spent over four weeks in altitude between 4500-6500m. Two weeks before and after exposure to hypoxia they performed supramaximal cycloergometic exercise (30s Wingate Test). After worming up, the subject began pedalling as rapidly as possible during 30s against a heavy resistance of 0,74N/kg body mass. The load was applied before the subject starts his work. During the test we measured: value of total work, peak and maximal power output, fatigue index, time to approaching to peak power, time of sustained the peak power. Body composition were estimated by bioimpedential method used the Tanita Body Fat Monitor/Scale. Results are shown in tables 1 and 2. Discussion/Conclusion: Our studies have shown that there is no significantly different changes in most of body compositions parameters between pre- and post expeditions period. There is only one significant difference with value of FAT measured in [%] of body mass or in [kg], and that may improved enhanced fatty acid metabolism during long lasting high-altitude stress. We also showed many significant differences between anaerobic performance parameters, contrary to what has been expected. Further investigations are needed to explain the effect of chronic hypoxia on decreases in anaerobic muscle power output and anaerobic metabolic pathways.